Ribosomal protein S3 is a novel negative regulator of non‐homologous end joining repair of DNA double‐strand breaks. Issue 6 (16th April 2020) - Park, Yong Jun; Kim, Tae‐Sung; Kim, Eun‐Ho; Kim, Hag Dong; Kim, Joon
Abstract: DNA double‐strand breaks (DSBs) are one of the most serious types of DNA damage. However, multiple repair pathways are present in cells to ensure rapid and appropriate repair of DSBs. Pathway selection depends on several factors including cell type, cell cycle phase, and damage severity. Ribosomal protein S3 (rpS3), a component of the 40S small ribosomal subunit, is a multi‐functional protein primarily involved in protein synthesis. rpS3 is also involved in the mediation of various extra‐ribosomal pathways, including DNA damage processing and the stress response. Here, we report that rpS3 is a novel negative regulator of non‐homologous end joining (NHEJ)‐mediated repair of DSBs. We found that rpS3 interacts with the Ku heterodimers of the DNA‐dependent protein kinase (DNA‐PK) complex and slows down NHEJ ligation reactions, ultimately triggering p53‐dependent cell death following treatment with high‐dose ionizing radiation. After DSB formation, DNA‐PK phosphorylates rpS3, which consequently reduces the binding of rpS3 to the Ku complex. We hypothesized that rpS3 may play a role in DSB repair by repressing NHEJ, while inducing other repair pathways, and by initiating DSB‐induced cell death in response to severe DNA damage.